Forecasting the use of chiropractic services within the Veterans Health Administration - Victoria A. Bensel; Kelsey Corcoran; Anthony J. Lisi (PLoS ONE, 2025)
Objective To model future use of chiropractic services and predict clinical resource needs within the Veterans Health Administration (VA) over the next 5 years. Methods A serial cross-sectional analysis of chiropractic use data from VA’s Corporate Data Warehouse for fiscal years (FY) 2017 through 2022 (10/1/2016-9/30/2022). We calculated the proportion of VA chiropractic users–via care provided on-station and/or purchased from Community Care Network (CCN) providers–compared to overall VA healthcare users for each FY. We calculated the historical year-over-year compound annual growth rate (CAGR), which was used to predict use in FY2023 through 2027 (10/1/2022-9/30/2027). Results VA’s chiropractic use rate increased from 1.4% in FY2017 to 3.5% in FY2022, at which point 2.0% of VA users received only CCN chiropractic care, 1.3% only on-station, and 0.2% both. During the 6-year observation period, the CAGRs were overall 17.9%, CCN only 23.8%, on-station only 12.4%, and both 27.7%. Using those rates to extrapolate, by the end of FY2027 overall use will be 8.9%, with 5.9% only CCN, 2.3% only on-station, and 0.6% both. Conclusion Overall use of VA chiropractic services is projected to more than double from FY 2022 to FY2027. These findings underscore the need for proactive resource planning to address the expected increased use of both CCN and on-station care.